Preservation of Traditional Art: The Case of the Nooraa Performance in Southern Thailand - Takako Iwasawa (Wacana Seni Journal of Arts Discourse, 2008)
This paper looks at the history of nooraa, a traditional performance art as well as a cultural symbol of contemporary Southern Thailand. It shows how nooraa is being preserved and how performers have transformed it and adapted it to modern Thai culture in order to maintain the art form. The nooraa dance is no longer restricted to those who come from a rich tradition of nooraa; instead, it is being performed and studied by the general public. Members of the general public, who used to be the audience, have become part of a new class of performers due to the introduction of cultural education within the education system. This is the result of a campaign led by the government to revitalise traditional culture at the national and local levels. This study elucidates how the general public and professional nooraa performers are both becoming involved in the movement for the preservation of traditional culture, and how, while they share the same goals, they are recreating tradition in many different ways.